Diagnostic Value of Magnetic Resonance Imaging in Fetal Lateral Ventriculomegaly and the Relationship Between the Degree of Isolated Lateral Ventriculomegaly and Neonatal Prognosis. Issue 1 (14th January 2020) - Zhao, Xiao-Min; Li, Xing; Li, Wen; Li, Shan-Shan; Chang, Ying
Abstract: Objective: To assess the value of magnetic resonance imaging (MRI) in fetal lateral ventriculomegaly diagnosed with ultrasound, and to study the relationship between the degree of isolated lateral ventriculomegaly and neonatal prognosis. Methods: The pregnancy information and outcomes of 97 cases of fetal ventriculomegaly were retrospectively reviewed in the Tianjin Central Hospital of Gynecology Obstetrics from January 2016 to December 2017. The maternal age was 18–42 years, and the fetal gestational age at diagnosis was 19 +4 to 37 +3 weeks. MRI and ultrasound were used to compared the diagnosis of fetal lateral ventriculomegaly and evaluated the development of the nervous system after birth. Results: Among 97 pregnancy cases, associated central nervous system malformations were observed in 36 cases on ultrasound or ultrasound + MRI. Central nervous system malformations were diagnosed with ultrasound in 15 cases (15/36, 41.7%) and with ultrasound + MRI in 25 cases (25/36, 69.4%). Pearson χ 2 test was used to compare the detection rates between the groups, and the difference was statistically significant ( P < 0.05). We followed up 61 cases of isolated lateral ventriculomegaly for 1–3 years after birth. According to the width of the lateral ventricle of the fetus in middle pregnancy, the subjects were grouped as follows: mild 33 cases (lateral ventricle width 10.0–12.0 mm), moderate 23 cases (lateral ventricle width 12.1–15.0 mm), and severe 5 cases (lateral ventricle width >15.0 mm). The rate of normal growth and development in the mild group was 90.9% (30/33), that in the moderate group was 69.6% (16/23), and that in the severe group was 40.0% (2/5), and the difference between groups was statistically significant ( P < 0.05). Conclusion: Ultrasound combined with MRI can detect more central nervous system malformations, and the degree of isolated lateral ventriculomegaly is closely related to fetal prognosis.